Molecular Dynamics Simulation of Amorphous Vanadium Pentoxide - Thu Nhan, Nguyen; Thi Lan, Mai; Thi Nam, Nguyen (VNU Journal of Science: Mathematics - Physics, 2022)
A molecular dynamics (MD) simulation has been carried out to explore the microstructure and diffusion pathway in amorphous vanadium pentoxide (V 2 O 5 ) materials at room temperature and ambient pressure. We showed that the simulated model is a mix of basic units VO5 and VO6 connected to each other via 2 or 3 bridging oxygens. In the simulated model, there exist regions without atoms (cavity) in the form of clusters or channels. We found that 87% large pores, larger than or equal to oxygen atoms, overlap to form the largest tube. Keywords: Vanadium pentoxide, amorphous, pore.